An analysis of nonnutritive calories from propofol, dextrose, and citrate among patients who are critically ill that are receiving continuous renal replacement therapy. Issue 8 (14th July 2022) - Li, Priscilla; Huang, Yingxiao; Wong, Alvin
Abstract: Background: Propofol, dextrose, and citrate infusions are necessary treatment modalities in the intensive care units (ICUs). They are, however, a potential source of nonnutritive calories (NNCs), which may cause overfeeding and adverse complications. The literature surrounding the role of NNCs is limited. We aimed to examine the energy contribution of NNCs. Our secondary aim is to assess the nutrition impact of NNCs, especially among patients receiving continuous renal replacement therapy (CRRT). Materials/Methods: We enrolled 177 mechanically ventilated patients admitted to medical‐surgical ICUs from August to December 2019. Patients were monitored over the first 7 days of admission. Infusion rates of enteral nutrition/parenteral nutrition and NNCs, as well as clinical characteristics, were examined. Patients receiving CRRT were compared with those without. Results: In total, 24% of patients additional energy from citrate. Patients received a maximum of 331 kcal from citrate, 492 kcal from propofol, and 992 kcal from dextrose per ICU day. CRRT group achieved higher total energy on the first 2 days (day 1: 55.1% vs 46.4%, P = 0.008; day 2: 73.2% vs 55.4%, P = 0.025). They also received higher mean NNCs on all days, except for day 1 ( P = 0.068). Conclusion: NNCs, especially citrate, are significant sources of energy. Patients receiving CRRT were more likely to be malnourished. There should be close monitoring and adaption of energy prescription accordingly to prevent overfeeding.